2018
DOI: 10.1002/er.4327
|View full text |Cite
|
Sign up to set email alerts
|

A parametric comparison of temperature uniformity and energy performance of a PEMFC having serpentine wavy channels

Abstract: Summary Proton exchange membrane fuel cells (PEMFCs) are regarded as alternative energy sources because they are environment friendly and deliver no harmful emission. As its reliability and power generating efficiency is largely influenced by the temperature distribution, it is necessary to improve the temperature uniformity which is crucial in PEMFCs. To this end, this numerical study presents an attempt to optimize the flow channels via introducing wavy shape flow channels at the ribs. The numerical model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The uniformity temperature distribution will have a great impact on the performance of fuel cells, the Joule heat and reaction heat generated inside the fuel cell during operation can lead to uneven temperature distribution, even local high temperature generated. 2,8 If the local temperature exceeds 100 C, high temperature steam makes the film break, leading to direct contact between hydrogen and oxygen, which may lead to explosion. Too large the temperature difference on the membrane, the generated thermal stress leads to the deformation of the proton exchange membrane and the falling off of platinum particles on the catalytic layer.…”
Section: Introductionmentioning
confidence: 99%
“…The uniformity temperature distribution will have a great impact on the performance of fuel cells, the Joule heat and reaction heat generated inside the fuel cell during operation can lead to uneven temperature distribution, even local high temperature generated. 2,8 If the local temperature exceeds 100 C, high temperature steam makes the film break, leading to direct contact between hydrogen and oxygen, which may lead to explosion. Too large the temperature difference on the membrane, the generated thermal stress leads to the deformation of the proton exchange membrane and the falling off of platinum particles on the catalytic layer.…”
Section: Introductionmentioning
confidence: 99%
“…1 The PEMFCs generally show high electrochemical performance in high relative humidity (RH) operating conditions and are utilized in fuel cell electric vehicles. 2 However, fully humidified conditions are not recommended, because excessive water vapor leads to condensation. Studies have shown uniform and high performance in 70% RH conditions, but irregular performance due to condensation under highly humidified conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolyte membrane fuel cell (PEMFC) is regarded as an ideal power source for vehicles because of its high energy conversion efficiency, high energy density, and zero‐emission 1‐5 . In the past few decades, PEMFC has made breakthroughs in terms of mileage, system life, and cost 6‐10 .…”
Section: Introductionmentioning
confidence: 99%